Neurologic Music Therapy via Telehealth: A Survey of Clinician Experiences, Trends, and Recommendations During the COVID-19 Pandemic - Cole, Lauren Patricia; Henechowicz, Tara Lynn; Kang, Kyurim; Pranjić, Marija; Richard, Nicole Marie; Tian, Gloria L. J.; Hurt-Thaut, Corene (Frontiers in Neuroscience, 2021)
This cross-sectional survey investigated the transition of Neurologic Music Therapy (NMT) services from in-person (pre-COVID-19) to telehealth (since COVID-19) to 1) determine whether the use of an NMT paradigm contributes to the successful transition of therapy services to telehealth, 2) identify which NMT domains and techniques are transferable from in-person to telehealth, 3) identify whether there are differences in the transition of NMT services across different employment settings, and 4) evaluate the potential benefits and challenges of telehealth NMT. An online survey comprised of forty-nine closed and open-ended questions were distributed by the Academy of Neurologic Music Therapy to 2778 NMT affiliates worldwide. The survey sought information on demographics, telehealth perceptions, technology, assessment, clinical practice, safety, and caregiver involvement. Quantitative and qualitative analyses were applied. Eighty-one participants answered the survey and the sixty-nine who completed the survey in its entirety were included in the analysis. Results indicated that the frequency of NMT technique usage had no impact on the overall number of clinical hours retained over telehealth. Correlation analysis revealed an association between more frequent NMT usage and perceived likelihood of using telehealth in the future (i.e., once COVID-19 is no longer a major threat), as well as with fewer group sessions lost over telehealth. All NMT domains transferred to telehealth, although within the sensorimotor domain, fewer therapists implemented rhythmic auditory stimulation for telehealth sessions compared to in-person. Overall, NMTs experienced less hours for telehealth compared to in-person regardless of employment setting. Technological challenges were notable drawbacks, while major benefits included the ability to continue providing NMT when in-person sessions were not possible, increased accessibility for remote clients, and positive outcomes related to increased caregiver involvement. Based on the results, our recommendations for implementing telehealth in Neurologic Music Therapy include integrating telehealth into routine care, mitigating safety concerns, identifying those who could benefit most from remote delivery, involving caregivers, and developing/sharing resources for telehealth NMT.